Anguilla anguilla L. genotoxic and liver biotransformation responses to abietic acid exposure - Maria, V. L. (2020)
Adult eels (Anguilla anguilla L.) were exposed for 8, 16, 24, and 72 h to 0, 0.1, 0.3, 0.9, and 2.7 microM abietic acid (AA). Genotoxicity was measured as erythrocytic nuclear abnormalities (ENA), as well as DNA strand breaks in blood and liver. Liver cytochrome P450 (P450) content, liver ethoxyresorufin O-deethylase (EROD), and glutathione S-transferase (GST) activities were determined as biotransformation biomarkers. Liver alanine transaminase (ALT) activity was also measured as an indication of tissue damage. Low AA concentrations, such as 0.1 and 0.3 microM, result in a delayed induction of A. anguilla L. liver EROD activity, whereas the higher AA concentration (2.7 microM AA) also has a delayed effect probably as a consequence of liver tissue high inhibitory concentration. The current eel liver GST activity results demonstrate that only low AA concentrations promote liver increases in GST, whereas high AA concentrations, such as 0.9 and 2.7 microM, do not alter it. The results concerning eel liver ALT activity indicate that significant liver damage is induced by high AA concentrations, such as 2.7 and 0.9 microM. The eel ENA result analysis reveals that AA is a weak ENA inducer in A. anguilla L. Blood DNA integrity results suggest that low AA concentrations promote late decreases in blood DNA integrity; nevertheless, high AA concentrations are early blood genotoxic inducers compared with low AA doses. According to the present research results with respect to eel liver DNA damage, all of the AA exposure concentrations decreased liver DNA integrity.